Case studies: Effects of beef, whey and carbohydrate supplementation in female master triathletes - Mehta, K. J.; Seijo, M.; Larumbe-Zabala, E.; Ashrafi, N.; Christides, T.; Karsten, B.; Nielsen, B. V.; Naclerio, F. (Journal of Human Sport & Exercise, 2019)
Appropriate nutritional supplementation is crucial for athletic performance, particularly for female endurance athletes as their numbers steadily increase. This report involves a set of six case studies examining the effects of ingesting a post-workout supplement containing beef, or whey or carbohydrate on iron status, blood indices, muscular thickness, peak oxygen consumption (VO2 max) and body composition in six female masters-age (> 35 years old) triathletes. Over a 10-week training period, a 20 g supplement was ingested immediately post workout or during breakfast on the non-training days. Of the six analyzed cases, two ingested protein powder from beef, two consumed whey, and two consumed maltodextrin. Data showed that concomitant with increased dietary iron ingestion, levels of the iron-storage protein ferritin increased in beef-consumers (by 56% and 74 %) and carbohydrate-consumers (by 71% and 27 %), but decreased in whey-consumers (by 55% and 36%). Contrastingly, the effect on transferrin levels was highly variable between participants in each supplementation case. The whey-consumers showed reduced RBC count (by 6%), hematocrit (by 8%) and red blood cell distribution width (by 14% and 5%). While one beef-consumer showed a remarkable 34% increase in platelets, the whey and carbohydrate-consumers showed reduced platelets, but increased neutrophil:lymphocyte ratio. Vastus medialis thickness reduced in carbohydrate-consumers (by 6% and 5%), unlike the beef and whey-consumers. Females consuming beef increased iron stores and platelets, while those ingesting whey were unable to maintain specific RBC indices. Only the four athletes ingesting protein-containing supplements were able to maintain muscle thickness, thereby averting muscle loss.